ROLE OF BUFFER FLUIDS IN CEMENTING OF OIL AND GAS WELLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the role of spacer fluids in cementing oil and gas wells. It is shown for what purpose it is used in the cementing of oil and gas wells to separate the flows of drilling and cement fluids injected into the well. With the accumulation of experience in the use of spacer fluids for cementing wells, their type, composition and requirements for them have increased. Currently, spacer fluids must provide high quality separation of the flow of drilling and cement fluids in the tubular and annular space when cementing deep wells.